2001
DOI: 10.1111/j.1469-7793.2001.t01-1-00801.x
|View full text |Cite
|
Sign up to set email alerts
|

Gastric distension‐induced pyloric relaxation: central nervous system regulation and effects of acute hyperglycaemia in the rat

Abstract: Pyloric sphincter tone plays an important role in the regulation of gastric emptying. Non-adrenergic, noncholinergic (NANC) innervation to the pylorus is predominantly inhibitory and mediates relaxation of the sphincter (Anuras et al. 1974). A high density of NOSimmunopositive nerve cells and fibres has been demonstrated in the pylorus (Ekblad et al. 1994), and significant reduction of NOS activity of the pylorus has been demonstrated in infantile hypertrophic pyloric stenosis (Vanderwinden et al. 1992). It ha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
42
0
1

Year Published

2003
2003
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 40 publications
(44 citation statements)
references
References 43 publications
(66 reference statements)
1
42
0
1
Order By: Relevance
“…Animal studies demonstrate pyloric relaxation induced by gastric distension is significantly reduced by subdiaphragmatic vagotomy, thereby prohibiting food passage [24]. Furthermore, demyelinating disease in the medullary region of the brainstem, presumably the vagal nerve nuclei, secondary to multiple sclerosis, has been correlated with gastroparesis and abnormal gastric emptying studies [25].…”
Section: Gut Pathophysiologymentioning
confidence: 98%
“…Animal studies demonstrate pyloric relaxation induced by gastric distension is significantly reduced by subdiaphragmatic vagotomy, thereby prohibiting food passage [24]. Furthermore, demyelinating disease in the medullary region of the brainstem, presumably the vagal nerve nuclei, secondary to multiple sclerosis, has been correlated with gastroparesis and abnormal gastric emptying studies [25].…”
Section: Gut Pathophysiologymentioning
confidence: 98%
“…Gastric distension-induced pyloric relaxation is significantly reduced by subdiaphragmatic vagotomy, hexamethonium, and l-NAME, but not by splanchnicotomy and guanethidine. 53 This suggests that gastric distension-induced pyloric relaxation is mediated via the vagus and NO neurons.…”
Section: Pyloric Sphinctermentioning
confidence: 99%
“…It has been reported that metabolites of L-arginine mediate neuronal inhibition of canine pyloric motor activity in vivo (Allescher et al, 1992) and facilitate gastric emptying by inhibiting pyloric contractions (Orihata and Sarna, 1994). Gastric distension-induced pyloric relaxation appears to be mediated via a vago-vagal reflex and NO release in the rat (Ishiguchi et al, 2001). The primary site of action of nitrergic mechanisms on the gastric fundic tone in conscious dogs is likely to be at a presynaptic level on the vagal cholinergic efferent nerves (Paterson et al, 2000).…”
mentioning
confidence: 99%